Peningkatan Perilaku Kesehatan Masyarakat terhadap Bahaya ISPA di Wilayah Kerja Puskesmas Alalak Tengah Kota Banjarmasin - Mahmudah Mahmudah; Yeni Riza; M Bahrul Ilmi (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
ISPA is a disease that often occurs with the arrival of the dry season and increasing forest and land fires. Various attempts were made to control ISPA, one of which was handling respiratory problems due to smog. In PuskesmasAlalak Tengah, ISPA is the first of 10 diseases in the last 2 years. In addition, some people still consider trivial diseases of ISPA and are not accustomed to wearing masks when doing activities and activities. Therefore, community service needs to be held to increase community awareness of ISPA. The aim of the activity is to increase public health knowledge and behavior towards the danger of ISPA. The target activity is the people in Alalak Tengah Village through counseling using leaflet and poster media. After being educated through counseling and evaluating the participants, an increase in public health behavior towards the danger of ISPA it appears from the motivation and enthusiasm of the participants to use masks, so that they are more aware of the risk of ISPA transmission